Development of an IoT-Based Smart Waste Bin with Automated Operation and Capacity Monitoring - Pria Intiadi; Gunawan Sihaloho; Al Fauzan Dito Prasetyo; Budi Wibowo (Sultan Publisher, 2025)
In many public facilities, waste bins are still monitored through routine manual checks, which often results in delayed collection when the bin reaches its capacity. This situation is commonly found in campus park areas, where waste overflow reduces cleanliness and user comfort. This research aims to design and evaluate an IoT-based smart waste bin system that integrates automated lid operation and real-time capacity monitoring to improve waste management efficiency in public spaces. The system uses an ESP32 microcontroller together with an ultrasonic sensor to estimate the waste level and a Passive Infrared (PIR) sensor to detect human presence near the bin. An OLED display is included to show local system status, while remote monitoring and notifications are handled through the Blynk Console platform. The methodology involves system design, algorithm development, and simulation-based testing using the Wokwi platform. During operation, the bin lid opens when motion is detected and closes automatically after a short period. The waste level is observed continuously, and a notification is sent when the predefined capacity threshold is reached. Simulation results demonstrate an average accuracy of 98.8% for capacity detection with an absolute error of 1.2%. The system successfully performed automated lid operations, real-time status display on OLED, RGB LED status indication, and timely notifications via Blynk Console. These findings indicate that the proposed IoT-based smart waste bin can significantly enhance waste management operations in public areas by enabling proactive collection scheduling and reducing overflow incidents, thereby contributing to improved environmental hygiene and operational efficiency.